TIME BUDGET PREASURE AND TURNOVER INTENTION WITH DYSFUCTIONAL ACCOUNTANT BEHAVIOR - Jamaluddin Majid; Ambo Asse (International Journal of Economics Management and Social Science, 2018)
A public accountant as a profession that provides assurance services about historical financial report information to the public is required to have adequate accounting knowledge and accounting skills as well as personal qualities. Such personal qualities will be reflected in his professional behavior. Professional behavior of public accountant one of them embodied in the form of avoid dysfunctional behavior of accountant. dysfunctional behavior is related to time budget pressure and turnoer intention. A high level of time budget pressure will encourage auditors to perform dysfunctional behaviors. The desire to quit working is also judged to affect the irregularities of auditor behavior. There is a significant positive correlation between intention turnover and dysfunctional audit behavior due to decreased fears of possible sanctions if such behavior is detected.